The effect of Spinacia oleracea dye absorption time on ZnO-based dye-sensitized solar cells’ electrical performance - Norizan, Mohd Natashah; Mohamad, Ili Salwani; Magiswaran, Kaiswariah; Mahmed, Norsuria; Idris, Siti Norhafizah; Abal Abas, Zuraida (Universiti Malaysia Perlis, 2022)
Dye-sensitized solar cells (DSSC) have attracted much attention over the past 20 years due to their significance in energy conversion. However, the dye soaking time may significantly impact the efficacy of the photoanode semiconductor to carry the electronic charge to which the dye molecules adhere. An optimized dye soaking time may prevent the recombination of photo-excited electrons that are injected into the semiconductor of the DSSC. This study scrutinized the dependence of the zinc oxide (ZnO) photoanode soaking time of Spinacia oleracea (spinach) dye on the photocurrent-voltage characteristics. The ZnO film layer (photoanode) was prepared with commercial ZnO nanopowder and applied onto a fluorine-doped tin oxide (FTO) glass substrate using the doctor blade method. The prepared DSSCs’ were subjected to a variety of characterizations, including current density-voltage (J-V) characterization, UV-visible characterization, scanning electron microscope (SEM), and X-ray diffraction (XRD). Comparing four variations of dye soaking time, ZnO-based DSSC photoanode soaked in the dye for an hour achieved an optimum efficiency of 0.03 %. This study proved that the efficiency of a DSSC can be improved by optimizing the dye soaking time.